Inmunocytochemical expression of dopamine-related transcription factors Pitx3 and Nurr1 in prenatally stressed adult rats - Katunar, Maria Rosa (2008)
Rats exposed to different types of stress during the last week of pregnancy produce offspring that show severe anomalies in neural development and brain morphology. We have previously reported that prenatal stress (PS) induced by immobilization increases D2-type dopamine (DA) receptor levels in the adult offspring, with a concomitant reduction in DA release in prefrontal cortex after amphetamine stimulation. It has recently been identified two transcription factors, Nurr1 and Pitx3, which are expressed at critical moments of DA neurons differentiation. Their genetic expression is activated immediately after these neurons determination and maintained through adult life. Nurr1 regulates several proteins that are required for dopamine synthesis and regulation, and Pitx3 is specifically involved in the terminal differentiation and maintenance of dopamine neurons. Employing an inmunocytochemistry approach, we studied the expression of Nurr1 and found a ubiquitous distribution in cerebral cortex, hippocampus, thalamus, amygdala and midbrain whereas Pitx3 remains restricted to the mesencephalic DA neurons such as substantia nigra (SN) and ventral tegmental area (VTA). Our results show that the expression of both Nurr1 and Pitx3 increased in prenatally stressed adult offspring in the VTA area, whereas no changes were observed in SN areas. It might be hypothesized that the increase of the specific dopaminergic transcription factors might be a compensatory mechanism to counteract the reduction in dopamine levels previously observed as a consequence of prenatal stress.